2018
DOI: 10.1126/scisignal.aam8939
|View full text |Cite
|
Sign up to set email alerts
|

RORγt limits the amount of the cytokine receptor γc through the prosurvival factor Bcl-x L in developing thymocytes

Abstract: The cytokine receptor subunit γc provides critical signals for T cell survival and differentiation. We investigated the molecular mechanism that controls the cell surface abundance of γc during T cell development in the thymus. We found that the amount of γc was low on CD4CD8 double-positive (DP) thymocytes before their positive selection to become mature T cells. The transcription factor RORγt was abundant in immature DP thymocytes, and its loss resulted in an increase in the abundance of surface γc, specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…Up-regulation of expression of survival-related proteins is one of the known mechanisms to promote thymocyte survival in this context. Well-studied examples include the Bcl-2 family prosurvival proteins Bcl-xL, whose stage-specific enrichment promotes the survival of DP thymocytes (6). In addition to regulations at the level of gene expression, further studies revealed that posttranslational modifications such as Ser/Thr phosphorylation of prosurvival proteins is also vital for thymocyte survival.…”
mentioning
confidence: 99%
“…Up-regulation of expression of survival-related proteins is one of the known mechanisms to promote thymocyte survival in this context. Well-studied examples include the Bcl-2 family prosurvival proteins Bcl-xL, whose stage-specific enrichment promotes the survival of DP thymocytes (6). In addition to regulations at the level of gene expression, further studies revealed that posttranslational modifications such as Ser/Thr phosphorylation of prosurvival proteins is also vital for thymocyte survival.…”
mentioning
confidence: 99%
“…Although these results indirectly support a RORγt requirement for CD138 expression, we consider it unlikely that RORγt expression is sufficient to induce CD138 expression on all T lineage cells. As such, we found that immature double-positive thymocytes, which comprise the main cell population in the thymus, expressed large amounts of RORγt but did not induce CD138 ( Figure 1A ) ( 23 ). These data indicated that CD138 expression is clearly associated with RORγt expression but that cellular factors other than RORγt also play roles in the induction of CD138 expression in T cells.…”
Section: Resultsmentioning
confidence: 84%
“…To this end, we examined thymic i NKT cells of RORγt-transgenic (RORγt Tg ) and WT littermate BALB/c mice for surface CD138 expression. RORγt Tg mice have been previously described ( 23 ), and they express the murine RORγt cDNA under the control of the proximal Lck promoter. Accordingly, all thymocytes, including thymic i NKT cells, are forced to express RORγt ( Supplemental Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…1C ). Furthermore, the forced expression of RORγt ( Ligons et al, 2018 ), the master transcription factor of NKT17 cell development and function ( Tsagaratou, 2019 ), dramatically increased both the frequency and number of DR3-expressing i NKT cells ( Figure 1D ). These results suggested that DR3 expression is controlled downstream of RORγt so that all DR3 + thymic i NKT cells of RORγt Tg mice also expressed CD138 ( Figure 1D; Figure 1–figure supplement 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…BALB/cAnNCrl and C57BL/6 mice were purchased from the Charles River Laboratories. CD138-deficient ( Sdc1 −/− ) mice and RORγt Tg mice were previously described ( Alexander et al, 2000; Ligons et al, 2018; Luo et al, 2021 ), and these animals were backcrossed in-house onto BALB/cAnNCrl background before analyses. Foxp3-DTR/EGFP mice were obtained from the Jackson Laboratory and maintained on BALB/cAnNCrl background ( Lahl et al, 2007 ).…”
Section: Methodsmentioning
confidence: 99%